Identification of a damage criterion of a highly porous alumina ceramic. (1st April 2016) - Staub, D.; Meille, S.; Le Corre, V.; Rouleau, L.; Chevalier, J.
Abstract: This paper aims at identifying the multiaxial compression behavior of highly porous ceramics used as catalyst supports. For this purpose, instrumented spherical indentation tests are performed, together with uniaxial and hydrostatic compression tests. A transition from a brittle to a damageable behavior with densification of the material is noted when increasing the triaxiality of the test. The collapse of large pores is shown as being responsible for the densification phenomenon, as confirmed by SEM and mercury intrusion porosimetry. A multiaxial damage criterion is proposed and identified thanks to a numerical finite element model. The results described in this paper coupled with a previous work (Staub et al., Oil and gas science and technology 2015, vol 70, n° 3, 475–86 ) on the behavior of the same material under tension loading, allow for the first time to define a multiaxial criterion both in tension and in compression for highly porous ceramics. These materials are shown to present a typical behavior of dense ceramics in tension, whereas in compression, their behavior is close to that of porous rocks. Graphical abstract: